2018
DOI: 10.1111/aphw.12143
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Youth Mental Health via Text‐Messages: A New Zealand Feasibility Study

Abstract: This interactive e-health promotion strategy seemed to promote strong engagement and showed promising effectiveness with young people, with some challenges to feasibility due to the labor intensive nature of sending and responding to a large number of text-messages. The importance of carefully considering risk management strategies when developing such programs was also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 65 publications
0
5
0
1
Order By: Relevance
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…Studies reported (in descending order of frequency) on anxiety features (87 articles; 29.5%), affective symptoms (65 articles; 22.0%), other emotional and behavioral problems (62 articles; 21.0%), conduct problems (59 articles; 20.0%), general psychological distress (52 articles; 17.6%), alcohol use (42 articles; 14.2%), externalizing behaviors, (31 articles; 10.5%), tobacco use (32 articles; 10.8%), internalizing behaviors (25 articles; 8.5%), cannabis use (23 articles; 7.8%), ADHD features (21 articles; 7.1%), interpersonal violence (14 articles; 4.7%), eating-related problems (13 articles; 4.4%), consequences of alcohol use (12 articles; 4.1%), PTSD features (6 articles; 2.0%), sleep-related problems (6 articles; 2.0%), and impaired functioning (5 articles; 1.7%) (Supplemental Table 3, http://links.lww.com/HRP/A158). 44–133, 134–231, 232–332 …”
Section: Resultsmentioning
confidence: 99%
“…Text messaging is easily scalable and can work on nearly any mobile phones today—with youth willing to engaging around mental health text messages. 16 There is a rich legacy of web-based programs for youth mental health 17 and a stream of new tools using today’s social networking features. 18 Computer and video games are also receiving recognition as tools to improve mental health 19 and hold unique potential given their high rates of engagement.…”
mentioning
confidence: 99%
“…An experimental study conducted on promoting youth mental health via text messages on 136 older adolescents and young adults showed positive changes over the course of the program. 20 These changes were noticed in the subjects' general sense of gratitude, subjective well-being, and in the reduction of depressive symptoms. The results showed that those with higher levels of depressive symptoms in fact, benefited more from the gratitude program.…”
Section: Studies Concerning Technology-based Gratitude Interventions ...mentioning
confidence: 95%